ANALISIS KUALITAS JASA DALAM MENINGKATKAN KEPUASAN KONSUMEN DI BAKER STREET CAFE BANDUNG - Adisty Arindiaty; Merita Bernik (Jurnal Bisnis Terapan, 2017)
The globalization at present has brought a great impact on the businessworld development. The alternative selected products offered to the customersvary and make the customer expectation more to get something they want.This condition requires for every company to try to give the best satisfactionto its customers. This is done in order that the business people can maintaintheir business in facing the tough competition. This research tried to assessthe customer satisfaction toward the service quality of Baker Street Café,Bandung. The research method used here was the descriptive qualitativeone, using sampling technique, that is, the technique of probability samplingand purposive sampling method. The data were collected using a field studyconsisted of observation, interviews, questionnaires, and literature study. Themethod of performance analysis was used to assess the customer satisfaction.The result of the study showed that the service quality provided by Baker StreetCafé, Bandung was categorized as “ good” with the average highest score for thedimension of reliability by 4,074 and the lowest for dimension of empathy andassurance by 3,93. At this customer expectation level, the average highest scorewas for the dimension of assurance by 4,55 and the lowest for the dimension ofreliability by 4,5, which means that the customers were unsatisfied becausetheir expectation was higher than the performance demonstrated by BakerStreet Café, Bandung.